Good kids from bad neighborhoods : successful development in social context - Elliott, Delbert S.; Menard, Scott W.; Rankin, Bruce H. (Bruce Howard); Elliott, Amanda; Huizinga, David; Wilson, William J., 1935- (New York : Cambridge University Press, 2006)
This is a study of successful youth development in poor, disadvantaged neighborhoods in Denver and Chicago - a study of how children living in the worst neighborhoods develop or fail to develop the values, competencies and commitments that lead to a productive, healthy responsible adult life.
Growing up in disadvantaged neighborhoods -- Growing up in Denver and Chicago : the MacArthur neighborhood study -- Good and bad neighborhoods for raising children -- The effects of growing up in a bad neighborhood : initial findings -- Critical dimensions of neighborhood organization and culture -- The effects of neighborhood organization and culture -- Family influences : managing disadvantage and promoting success -- School climate and types of peer groups -- What matters most for successful youth development? -- Successful development in disadvantaged neighborhoods.
Includes bibliographical references (pages 353-380) and indexes.
Print version record.
eBooks on EBSCOhost
Keywords: Youth with social disabilities -- United States; Community organization -- United States; Children -- United States -- Social conditions; Neighborhoods -- United States; Jeunes socialement défavorisés -- États-Unis.; Organisation communautaire -- États-Unis.; Enfants -- États-Unis -- Conditions sociales; POLITICAL SCIENCE -- Public Policy -- Social Services & Welfare; POLITICAL SCIENCE -- Public Policy -- Social Security; Children -- Social conditions; Community organization; Neighborhoods; Youth with social disabilities; United States; Electronic books; Electronic books